New insights into the evolution of bacterial community during the domestication of phthalate-degrading consortium. (20th June 2021) - Huang, Xue-Jing; Du, Huan; Deng, Xiao-Long; Chen, Yong-Hong; Xiang, Lei; Li, Yan-Wen; Li, Hui; Mo, Ce-Hui; Cai, Quan-Ying; Zhao, Hai-Ming
Abstract: The selective enrichment culture technique is widely used in domestication of pollutant-degrading microorganisms. However, very little information is available regarding the evolution and interaction of microbial communities during the domestication. For the first time, successional variation of bacterial community and metabolism were investigated during the enrichment culture of a phthalate-degrading consortium. Results showed that the content of extracellular polymeric substances (EPS) increased significantly ( p  < 0.05) during the domestication, especially the polysaccharide, playing an important role in protecting the consortium against phthalate toxicity. In contrast, significant ( p  < 0.05) and successional decreases were observed in bacterial richness and diversity with the increasing concentrations of phthalate. Finally, Proteobacteria (60.8%) and Bacteroidetes (12.4%) associated with phthalate tolerance and degradation became the dominant phyla. Actinobacteria and Acidobacteria phyla dominated in the initial activated sludge and then gradually reduced at the late stage of domestication. Microbial interaction networks revealed that the mutualism and competition coexisted among members of the bacterial consortium due to the occupation of different niches. This study would contribute to the optimization and development of enrichment culture techniques for boosting bioremediation on a knowledge-based control. Graphical abstract: Image 1 Highlights: A bacterial consortium was enriched for high efficient degradation of phthalates. The evolution of microbial community was clarified during the domestication. Significant variation occurred in the EPS secretion and bacterial community structure. Proteobacteria and Bacteroidetes related to PAE degradation became the dominant phyla. Mutualism and competition coexisted among members of the bacterial consortium.